XANES Study of Tribofilm Formation With Low Phosphorus Additive Mixtures of Phosphonium Ionic Liquid and Borate Ester - Vyavhare, Kimaya; Sharma, Vibhu; Sharma, Vinay; Erdemir, Ali; Aswath, Pranesh B. (Frontiers in Mechanical Engineering, 2021)
Development of low phosphorus engine oils is important to minimize phosphorus induced exhaust catalyst poisoning and resulting harmful emissions. In this study, low phosphorus oil formulations were prepared by using an ashless additive mixture of borate ester (SB) with ionic liquid composed of a phosphonium cation and phosphate anion (P_DEHP) at 350 ppm and 700 ppm phosphorus. Tribological properties of this binary additive system were evaluated using a reciprocating cylinder on flat test configuration. Favorable interaction between P_DEHP and SB resulted in a significant reduction in friction coefficient and wear volume, in particular for P_DEHP(700P) + SB oil blend. Time-scale analysis of tribofilm formation was determined by running the tribological experiments for 5, 15 and 60 min duration. Electrical contact resistance (ECR) results revealed that addition of P_DEHP at 350 ppm of phosphorus to SB at 500 ppm of boron can reduce the incubation time from 300 sec to 100 sec for stable tribofilm formation. X-ray absorption near edge spectroscopy (XANES) analysis of tribofilms indicates that tribofilm mechanism for additive mixtures of P_DEHP and SB initially involve the formation of boron oxide-based films, which later interacts with phosphorus to form boron phosphates in addition to iron phosphates. Incorporation of high amount of boron phosphates in addition to boron oxide/acid and iron phosphates in the tribofilms contributed to improved tribological performance of P_DEHP(700P) + SB oil. XANES results reveal that tribofilms formed due to interaction of SB and P_DEHP evolve to a cross-linked structure, wherein chain length of polyphosphates is increased with the increase in rubbing time.